Peran Advokat dalam Mewujudkan Akses Keadilan bagi Masyarakat Miskin - Fahrurrozi Fahrurrozi; Rusmadi Rusmadi (Legal Note, 2025)
The role of advocates in the legal system is not limited to serving as legal counsel in court proceedings; they also act as a vital bridge in realizing access to justice for all segments of society, including the poor, who often face significant obstacles in obtaining legal protection. The poor frequently encounter structural, financial, and informational barriers that prevent them from accessing justice equally. In this context, advocates carry both a moral and professional responsibility to provide legal assistance—whether through litigation or non-litigation—on a pro bono basis as a form of service to social justice. Through their involvement in legal aid institutions, legal education programs, and policy advocacy, advocates play a crucial role in narrowing the legal gap faced by vulnerable groups. Furthermore, the existence of regulations such as Law No. 16 of 2011 on Legal Aid provides a legal foundation that reinforces the obligation and legitimacy of advocates in assisting the poor. This study highlights how the active involvement of advocates can strengthen the principles of the rule of law and democracy, and promote the establishment of a more just and inclusive legal order. Using a juridical-sociological approach, this paper also identifies the challenges and strategies that can be undertaken to enhance the role of advocates in expanding the reach of legal aid and empowering the poor to fight for their rights before the law.